Assessment of potential risk factors and skin ultrasound presentation associated with breast cancer-related lymphedema in long-term breast cancer survivors - Md Yusof, Khairunnisa’; Avery-Kiejda, Kelly A.; Ahmad Suhaimi, Shafinah; Ahmad Zamri, Najwa; Rusli, Muhammad Ehsan Fitri; Mahmud, Rozi; Mohd Saini, Suraini; Ibraheem, Shahad Abdul Wahhab; Abdullah, Maha; Rosli, Rozita (Multidisciplinary Digital Publishing Institute, 2021)
Breast cancer has been reported to have the highest survival rate among various cancers. However, breast cancer survivors face several challenges following breast cancer treatment including breast cancer-related lymphedema (BCRL), sexual dysfunction, and psychological distress. This study aimed to investigate the potential risk factors of BCRL in long term breast cancer survivors. A total of 160 female breast cancer subjects were recruited on a voluntary basis and arm lymphedema was assessed through self-reporting of diagnosis, arm circumference measurement, and ultrasound examination. A total of 33/160 or 20.5% of the women developed BCRL with significantly higher scores for upper extremity disability (37.14 ± 18.90 vs. 20.08 ± 15.29, p < 0.001) and a lower score for quality of life (103.91 ± 21.80 vs. 115.49 ± 16.80, p = 0.009) as compared to non-lymphedema cases. Univariate analysis revealed that multiple surgeries (OR = 5.70, 95% CI: 1.21–26.8, p < 0.001), axillary lymph nodes excision (>10) (OR = 2.83, 95% CI: 0.94–8.11, p = 0.047), being overweight (≥25 kg/m2) (OR = 2.57, 95% CI: 1.04 – 6.38, p = 0.036), received fewer post-surgery rehabilitation treatment (OR = 2.37, 95% CI: 1.05–5.39, p = 0.036) and hypertension (OR = 2.38, 95% CI: 1.01–5.62, p = 0.043) were associated with an increased risk of BCRL. Meanwhile, multivariate analysis showed that multiple surgeries remained significant and elevated the likelihood of BCRL (OR = 5.83, 95% CI: 1.14–29.78, p = 0.034). Arm swelling was more prominent in the forearm area demonstrated by the highest difference of arm circumference measurement when compared to the upper arm (2.07 ± 2.48 vs. 1.34 ± 1.91 cm, p < 0.001). The total of skinfold thickness of the affected forearm was also significantly higher than the unaffected arms (p < 0.05) as evidenced by the ultrasound examination. The continuous search for risk factors in specific populations may facilitate the development of a standardized method to reduce the occurrence of BCRL and provide better management for breast cancer patients.